2010
DOI: 10.1002/chem.200902422
|View full text |Cite
|
Sign up to set email alerts
|

Octakis(3‐azidopropyl)octasilsesquioxane: A Versatile Nanobuilding Block for the Efficient Preparation of Highly Functionalized Cube‐Octameric Polyhedral Oligosilsesquioxane Frameworks Through Click Assembly

Abstract: A one-step synthesis of octakis(3-azidopropyl)octasilsesquioxane from commercially available octakis(3-aminopropyl)octasilsesquioxane has been developed by a highly efficient diazo-transfer reaction under very mild conditions. Nonaflyl azide is shown to be a safer, cheaper and more efficient reagent for this transformation than the better known and generally used diazotransfer reagent triflyl azide. Octakis(3-azidopropyl)octasilsesquioxane is an excellent nanobulding block that can be readily octafunctionalize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
56
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 70 publications
(57 citation statements)
references
References 98 publications
1
56
0
Order By: Relevance
“…[11,14a,c,d] The versatility of this approach have been demonstrated in the preparation of the dye-POSS cluster 4 using the alkyne-substituted BDP fluorescent dye 3 (Scheme 2). [11] We have now studied the monofunctionalization of octa-azide 2 with the alkyne-substituted BDP dye 3 (Scheme 3), which we used previously for the preparation of dye-POSS cluster 4. This reaction would afford a POSS derivative 5 labeled with a single fluorescent probe and containing seven additional reactive azide groups ready for further functionalization with any molecule of interest having a terminal alkynyl group.…”
Section: Resultsmentioning
confidence: 99%
“…[11,14a,c,d] The versatility of this approach have been demonstrated in the preparation of the dye-POSS cluster 4 using the alkyne-substituted BDP fluorescent dye 3 (Scheme 2). [11] We have now studied the monofunctionalization of octa-azide 2 with the alkyne-substituted BDP dye 3 (Scheme 3), which we used previously for the preparation of dye-POSS cluster 4. This reaction would afford a POSS derivative 5 labeled with a single fluorescent probe and containing seven additional reactive azide groups ready for further functionalization with any molecule of interest having a terminal alkynyl group.…”
Section: Resultsmentioning
confidence: 99%
“…However, at the onset of our work, there was only a single example reported in the literature on the use of NfN 3 for the synthesis of an organic azide from a primary amine. [22] In our previous work, [12] we found that NfN 3 afforded higher and more reproducible yields of 2 (60-73%, which accounts for > 94% yield per amino group) than TfN 3 , under otherwise similar reaction conditions (Scheme 1). In order to assess the efficiency and general utility of NfN 3 as an advantageous and safer alternative to TfN 3 for the preparation of organic azides, we have now extended this study to a diverse set of amines, including simple alkylamines, aryl-A C H T U N G T R E N N U N G amines, amino acids, hexosamines, and complex aminoglycosides.…”
Section: Introductionmentioning
confidence: 82%
“…[12] We hoped that the mild conditions of the diazo transfer process would prevent nucleophile-induced cage rearrangements [13] that were expected to occur in alternative routes to 2 using nucleophilic substitution reactions with azide anion. [14] Compound 1, containing eight amino groups, provided a stringent test for the efficiency of the diazo transfer process.…”
Section: Introductionmentioning
confidence: 99%
“…1) and its reaction with a variety of alkynes. [25][26][27][28][29][30][31][32][33][34][35][36] The preparation of octa(3-azidopropyl)polyhedral oligomeric silsesquioxane POSS-(N 3 ) 8 requires a multi-step synthesis and suffers from a poor overall yield of 30-32%.…”
mentioning
confidence: 99%
“…The completion of the cycloaddition reaction was conrmed by MALDI-TOF and the reaction progress was monitored by Trastoy et al 32 have reported an efficient preparation of highly functionalised cubic-octameric POSS frameworks by click chemistry and the highest yield (96%) was obtained with the CuSO 4 $H 2 O/sodium ascorbate precatalyst system 20 using a biphasic organic solvent/water mixture at room temperature for 24 hours. We have used these reaction conditions for the functionalisation of the octa-alkyne-terminated POSS with azido-N-Fmoc-norleucine and 3 0 -azido-3 0 -deoxythymidine (Scheme 2).…”
mentioning
confidence: 99%